2003
DOI: 10.1038/nature01784
|View full text |Cite|
|
Sign up to set email alerts
|

Class 3 semaphorins control vascular morphogenesis by inhibiting integrin function

Abstract: The motility and morphogenesis of endothelial cells is controlled by spatio-temporally regulated activation of integrin adhesion receptors, and integrin activation is stimulated by major determinants of vascular remodelling. In order for endothelial cells to be responsive to changes in activator gradients, the adhesiveness of these cells to the extracellular matrix must be dynamic, and negative regulators of integrins could be required. Here we show that during vascular development and experimental angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
481
8
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 534 publications
(519 citation statements)
references
References 42 publications
26
481
8
1
Order By: Relevance
“…Accordingly, Sema3A seems to exert a permissive role on angiogenesis by inhibiting integrins-mediated adhesion of endothelial cells allowing their deadhesion. 50 The analysis of neuropilin-1 knockout mice has confirmed that neuropilin-1/ VEGF interaction is required for normal development of the vasculature. 51 A soluble neuropilin-1 isoform was identified and found to have robust antitumor activity.…”
Section: Classmentioning
confidence: 96%
See 1 more Smart Citation
“…Accordingly, Sema3A seems to exert a permissive role on angiogenesis by inhibiting integrins-mediated adhesion of endothelial cells allowing their deadhesion. 50 The analysis of neuropilin-1 knockout mice has confirmed that neuropilin-1/ VEGF interaction is required for normal development of the vasculature. 51 A soluble neuropilin-1 isoform was identified and found to have robust antitumor activity.…”
Section: Classmentioning
confidence: 96%
“…47,48 Interestingly, Sema3A binding to neuropilin-1 blocks the migration of endothelial cells. 49 However, several class 3 semaphorins, including Sema3A are also expressed by endothelial cells 50 and could have an autocrine action. Accordingly, Sema3A seems to exert a permissive role on angiogenesis by inhibiting integrins-mediated adhesion of endothelial cells allowing their deadhesion.…”
Section: Classmentioning
confidence: 99%
“…They were initially identified as repulsive axon guidance molecules that were required to direct neuronal axons to their appropriate targets. 9 More than 20 types of semaphorins have been identified, 10 and they have diverse functions in many physiological process, 11 including cardiogenesis, 12,13 angiogenesis, 14,15 vasculogenesis, 16 tumor metastasis, [17][18][19] osteoclastogenesis 20 and immune regulation. 21,22 In this review, we focus on two functional aspects of semaphorins, their roles in immune cell-cell interactions and immune cell trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that in neurons or cell lines, plexin engagement by semaphorins induces rearrangement of the actin cytoskeleton and inhibits integrinmediated cell adhesion, which leads to cellular retraction [13,14]. Although semaphorins and plexins are predominantly expressed in the nervous system, they can also be found in other tissues such as the vascular system [15] or the immune system [16]. In particular, Plexin C1 is expressed on DC and neutrophils (Walzer et al, in press).…”
Section: Introductionmentioning
confidence: 99%